Longitudinal Intraindividual Cognitive Variability Is Associated With Reduction in Regional Cerebral Blood Flow Among Alzheimer’s Disease Biomarker-Positive Older Adults - Holmqvist, Sophia L.; Thomas, Kelsey R.; Brenner, Einat K.; Edmonds, Emily C.; Calcetas, Amanda; Edwards, Lauren; Bordyug, Maria; Bangen, Katherine J. (Frontiers in Aging Neuroscience, 2022)
Intraindividual variability (IIV) across neuropsychological measures within a single testing session is a promising marker predictive of cognitive decline and development of Alzheimer’s disease (AD). We have previously shown that greater IIV is cross-sectionally associated with reduced cerebral blood flow (CBF), but not with cortical thickness or brain volume, in older adults without dementia who were amyloid beta (Aβ) positive. However, there is little known about the association between change in IIV and CBF over time. Therefore, we examined 12-month longitudinal change in IIV and interactions of IIV and AD biomarker status on changes in regional CBF. Fifty-three nondemented Alzheimer’s Disease Neuroimaging Initiative (ADNI) participants underwent lumbar puncture to obtain cerebrospinal fluid (CSF) at baseline and neuropsychological testing and magnetic resonance imaging (MRI) exams at baseline and 12-month follow-up evaluation. IIV was calculated as the intraindividual standard deviation across 6 demographically-corrected neuropsychological measures. Pulsed arterial spin labeling (ASL) MRI was acquired to quantify CBF and FreeSurfer-derived a priori CBF regions of interest (ROIs) were examined. AD biomarker positivity was determined using a published CSF p-tau/Aβ ratio cut-score. Change scores were calculated for IIV, CBF, and mean neuropsychological performance from baseline to 12 months. Hierarchical linear regression models showed that after adjusting for age and gender, there was a significant interaction between IIV change and biomarker-positivity (p-tau/Aβ+) for change in entorhinal and hippocampal CBF but not for the other ROIs. Specifically, increases in IIV were associated with reductions in entorhinal and hippocampal CBF among individuals who were biomarker-positive (n=21). In contrast, there were no significant associations between change in IIV and CBF among those who were biomarker-negative (n=32). Findings remained similar when analyses were performed adjusting for change in mean level of neuropsychological performance. Changes in IIV may be sensitive to changes in regional hypoperfusion in AD-vulnerable regions among AD biomarker-positive individuals, above and beyond demographics and mean neuropsychological performance. These findings provide further evidence supporting IIV as a potential marker of cerebrovascular brain changes in individuals at risk for dementia.